Respuesta :

Answer:

12

Step-by-step explanation:

Use the first two equations to solve for a and b.

multiply the second equation all the way through by -2

(-2)(a + 2b) = (-2)(7)

-2a -4b = -14  Add this to the first equation.

  -2a - 4b = -14

+   2a + 3b = 17

           -b = 3  Multiply both sides by -1

            b = -3 Plug -3 back into either of the 2 original equations to find a

a + 2b = 7

a + 2(-3) = 7

a - 6 = 7  Add 6 to both sides

a = 13

Now that we know a = -3 and b = 13, we can plug that into the third equation:

[tex]\frac{(3a + 5b)}{2}[/tex]

[tex]\frac{3(13) + 5(-3)}{2)}[/tex]

[tex]\frac{39 -15}{2}[/tex]

[tex]\frac{24}{2}[/tex] = 12